Informed consent in Malaysia : a socio legal study - Anisah Che Ngah (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2004)
The right of a person to control his body is a concept that has long been recognized in Malaysia under the law of torts. The purpose of requiring informed consent is to preserve that right in medical decision-making. Informed Consent is a relatively new concept in medical litigation cases. However in the late 1990's, it has become one of the important claims under negligence made against the doctor for failure to disclose relevant information to patients in respect of the treatment proposed. Whether Malaysia has begun to recognize patient's right to decision-making is yet to be seen. Furthermore the social-cultural relationship between doctors and patients had to be considered. In this respect, the researcher had conducted interviews with doctors and patients to gauge their reaction towards a shared process of decision-making, which is the central issue in the doctrine of informed consent. Findings suggest that in a society where primary health care is the main thrust to achieve health for all, the possibility of recognition of the rights of patients to receive information before making decisions about treatment appears remote. The findings also underscore the importance of incorporating aspects of informed consent as part of providing quality service to patients